The effect of an eight-week swimming training on capillary oxygen saturation and respiratory parameters - Devecio?lu, Sebahattin; Gökhan, Ismail (My University, 2011)
The purpose of this study was to investigate the effect of an eight-week swimming training programme, on capillary oxygen saturation and certain respiratoly parameters on sedentary men. A total of 80 voluntary sedentary men were included in the study; 40 men, with no active sports life, an average age of 26.2±2.8 years and an average height of 175±4 cm comprised the experimental group and 40 men, with an average age of 25.6±2.3 years and an average height of 176±3.4 cm comprised the control group. Members of the experimental group were accepted as non-swimmers and given an 8-week basic aerobic swimming training course, lasting 1.5 hours, three days a for eight week. The Capillary Oxygen Saturation (SO 2), Forced Expiration Volume (FEV 1), Forced Vital Capacity (FVC), Peak Expiratory Flow Rate (PEF), Forced Expiratoly Rate (FEF), Forced Expiratoly Centre Flow Rate (FEF 25-75), Forced Expiratory Time (FET), Vital Capacity (VC) and Maximum Voluntarily Ventilation (MVV) parameters of participants were measured. An statistical analysis program was used to analyse raw data obtained from conducted measurements. The chosen significance levels used to interpret the difference between variables were 0.01 and 0.05. The three measurement results taken for the experimental and control group during the eight weeks were compared. Analysis of variance was used for repetitive measurements to indentify the difference between the mean of the three measurements conducted from the experimental and control group; the Tukey-HSD test was used to determine which group caused the difference. When comparing means of SO 2 and respiratoly parameters, there was a statistically significant difference (p<0.05) between the mean of Measurement 1 for SO 2 and the mean of Measurement 2 for FEF of the experimental group in comparison to the mean of Measurement 1 for SO 2 and the mean of Measurement 2 for FEF of the control group. There was a statistically significant difference (p<0.01) between the means of Measurement 2 and Measurement 3 of SO 2, Measurement 3 of FEV, Measurement 2 and Measurement 3 of FVC, Measurements of PEF, Measurements of FEF, Measurements of FEF 25-75M, Measurement 3 of FET, Measurement 2 and Measurement 3 of VC and Measurement 3 of MVV. There was no statistically significant difference (p>0.05) between Measurement 1 and Measurement 2 of FEV 1, Measurement 1 of FVC, Measurement 1 and Measurement 2 of PEF, Measurement 1 of FEF, Measurement 1 and Measurement 2 of FEF 25-75, Measurement 1 and Measurement 2 of FET, Measurement 1 of VC and Measurement 1 and Measurement 2 of MVV. There was a statistically significant increase (p<0.01) in the capillary oxygen saturation and respiratoly parameters of participants in the experimental group; while there was no statistically significant difference between the capillary oxygen saturation and respiratoly parameters of participants in the control group. Study results illustrate that a regular and well-planned swimming training programme has a positive effect on the capillary oxygen saturation and respiratoly parameters of individuals. © IDOSI Publications, 2011.
Keywords: Oxygen saturation; Respiration; Swimming; Training